The Phenomenon of Bugis Tafsir on Islamization in Eastern Indonesia - Firdaus; HS, Muhammad Alwi; Parninsih, Iin; Abubakar, Achmad (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2025)
This article examines the phenomenon of Bugis tafsir, both written and oral, produced by the As'adiyah ulama during the Islamization of Eastern Indonesia. As’adiyah, the oldest pesantren in the region, played a crucial role in the dissemination and teaching of Islam. Within this process of Islamization, Bugis tafsir emerges as a significant subject of study, as tafsir was foundational to the establishment of this pesantren. This is exemplified by the Bugis tafsir Tafsir Surah Amma Bil-Lughah Al-Buqisiyyah by AGH. Muhammad As’ad Al-Bugisy, the founder of As’adiyah. Furthermore, Bugis tafsir has been developed in various forms by As'adiyah scholars, initiated by the early students of the pesantren’s founder. This article argues that local tafsir is not only part of the intellectual heritage of pesantren but also plays a vital role in shaping pesantren traditions. This study employs a phenomenological-historical approach, combining literature review and fieldwork. Its findings indicate that the production of Bugis tafsir is essential for the promotion and transmission of Islam in Eastern Indonesia through Qur'anic interpretation that engages with contemporary contexts. This role is particularly evident in three key aspects: (1) culturally rooted da'wah (religious outreach), (2) the preservation of intellectual and cultural heritage through interpretation, and (3) the safeguarding of the distinctiveness of pesantren and Bugis culture. These three primary functions highlight the importance of employing local languages in the process of Islamization through interpretation—especially within the cultural framework of the interpreter, particularly when the interpreter is a pesantren ulama.